Lipidomics is going great guns: Interview with Kai Simons about the power of shotgun lipidomics. Issue 10 (8th September 2014) - Kalvodova, Lucie; Simons, Kai
<x xml:space="preserve">Abstract</x> There are thousands of lipid species in living cells but we do not fully understand this diversity as it is not possible to pin down a specific function to each lipid species. Lipids have structural, metabolic and signaling functions. While signaling lipids can be understood and functionally characterized in a way similar to proteins, membrane lipids act collectively. This may have been one of the reasons for lipid neglect in the past. In order to understand the complexity of lipids in membranes, lipoproteins, body fluids, and organisms in general, we need to know the big picture which can only be delivered by modern lipidomic analyses. This has been increasingly appreciated mainly in the biomedical area. It is likely that interpretation of blood cell lipidomes will lead to the discovery of new biomarkers and lipid signatures of pathological states and cardiovascular disease risk, and so the era of HDL/LDL, TAG and cholesterol quantification may soon be over. But that is just one example. The motto of this year's Euro Fed Lipid Congress reads "From lipidomics to industrial innovation". Indeed with the advancement of mass‐spectrometry and computational approaches to analyze and understand big data, lipidomics is becoming more interesting for clinical applications and industry. <inline-graphic xlink:href="ark:/27927/pgh1fcj5pf7" content-type="ejlt201400405-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> The shotgun methodology is so robust, comprehensive, fast and quantitative that it can be taken to the clinic, food R&D and into other applications.